KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF HUKUM ISLAM DAN HUKUM PUBLIK - Patawari, Andi Yusri; Ridwan, Saleh; HL, Rahmatia; Rahmawati, St. (IAIN BONE, 2025)
The issue of domestic violence has received relatively little attention among legal experts, both in terms of regulation and implementation. This paper aims to raise awareness and explore the extent to which Islamic legal norms and public law align with the spirit of anti-violence, particularly within the household. This study employs a normative juridical approach. Data were collected through documentation techniques, focusing on Islamic legal literature such as the Quranic texts and Hadith, as well as classical fiqh texts and statutory regulations currently in force in Indonesia. The study reveals that acts of domestic violence are prohibited in Islam, which is consistent with the anti-violence principles embedded in Indonesian legislation related to acts of violence.